The Englishman from Lebedian' A Life of Evgeny Zamiatin - Curtis, J.A.E (Ars Rossica, 2013)
After Evgeny Zamiatin emigrated from the USSR in 1931, he was systematically airbrushed out of Soviet literary history, despite the central role he had played in the cultural life of Russia's northern capital for nearly twenty years. Since the collapse of the Soviet Union, his writings have gradually been rediscovered in Russia, but with his archives scattered between Russia, France, and the USA, the project of reconstructing the story of his life has been a complex task. This book, the first full biography of Zamiatin in any language, draws upon his extensive correspondence and other documents in order to provide an account of his life which explores his intimate preoccupations, as well as uncovering the political and cultural background to many of his works. It reveals a man of strong will and high principles, who negotiated the political dilemmas of his day-including his relationship with Stalin-with great shrewdness.